Nano-enhanced interface in carbon fibre polymer composite using halloysite nanotubes. (June 2018) - Jäger, Miriam; Zabihi, Omid; Ahmadi, Mojtaba; Li, Quanxiang; Depalmeanar, Andreas; Naebe, Minoo
Abstract: The carbon fibres (CFs) sizing has a crucial impact on final properties of CFs reinforced polymer composites. Herein, an industrially-adaptable process for sizing of CFs was employed through a dip-coating process which includes using epoxy sizing solutions mixed with halloysite nanotubes (HNTs). Potential changes in the mechanical properties of the CFs and the characteristics of the resulting composites were evaluated. Epoxy sizing containing various concentrations of HNTs changed the surface roughness, and friction of CFs. The obtained results demonstrated that HNTs does not significantly affect the tensile strength of CFs, however, surface energies, obtained by an inverse gas chromatography technique, are increased. To demonstrate the effect of HNTs on the fibre/epoxy matrix interactions, single fibre fragmentation tests (SFFT) were conducted and consequently apparent interfacial shear strength (IFSS) were calculated. The IFSS increased up to 23% compared to a pure sized CFs and up to 61% compared to an unsized-CFs.